Developing an evaluation framework for assessing the impact of recovery colleges: protocol for a participatory stakeholder engagement process and cocreated scoping review - Sophie Soklaridis; Sanjeev Sockalingam; Terri Rodak; Holly Harris; Elizabeth Lin; Sam Gruszecki; Kenya A Costa-Dookhan (BMJ Open)
Introduction Recovery colleges (RCs) are mental health centres aimed at equipping people with skills to live a meaningful life despite the presence of mental distress. Unique to them is the aspect of cocreation; RCs are designed collaboratively with people of lived experiences of mental health and addictions and care providers. Despite established benefits, there remains a lack of empirical evidence on how RCs work and on their impact.Aims We aim to address this gap by designing a cocreated evaluation framework for RCs. This will be accomplished by engaging RC student/facilitators to provide perspectives on RCs/RC evaluation and cocreate a scoping review identifying evaluation gaps in the literature. Themes identified through these processes will form the evaluation framework.Methods and analysis Two methodologies will be used to explore RC evaluation: student/facilitator engagement and a scoping review of current published and grey literature on RC evaluation. Engagement will be achieved using a participatory action research approach consisting of informant interviews of ~25 RC students/facilitators across Canada, which will be thematically analysed. The scoping review will follow methodology described by Arksey and O’Malley modified to support cocreation. Concurrent conducting of the engagement process and scoping review will allow RC students and peer facilitators the opportunity to shape RC evaluations, address gaps in the literature and codesign an evaluation framework focused on recovery-oriented processes and outcomes mattering most to RCs students/facilitators.Ethics and dissemination Ethics approval was received for the RC student/facilitator engagement component from the Centre for Addictions and Mental Health Research Ethics Board (#042–2020) and Ontario Shores Centre for Mental Health Sciences (#20–013-B). Scoping review results will be copresented through national and international medical education conferences and published in open-access peer-reviewed journals. Furthermore, a dissemination strategy on evaluation for the national RC community will be created.